CT density of cervical thymus, in comparison with mediastinal thymus - Anitha Sen (Insights into Imaging, 2019)
Abstract Objectives Cervical component of thymus is noted more in children and young adults than in older age group. CT texture (lobules of soft tissue interspersed with fat), similarity with CT density of mediastinal thymus and continuity with mediastinal thymus on sagittal/coronal images, are given as the criteria for diagnosis of the cervical thymus. But CT densities of cervical and mediastinal components of the thymus may vary. The purpose of our study was to compare CT densities of cervical and mediastinal parts of the thymus, in cases where ultrasonography correlation was available. Methods We retrospectively identified 22 patients who had undergone CT between May 2015 and May 2017 and in whom ultrasonography (USG) correlation was available. CT densities of cervical and mediastinal components of thymus were measured. Results 1.CT density of cervical thymus is lower than the CT density of mediastinal thymus by ~ 25 HU.2.There is a moderate positive correlation between CT densities of cervical and mediastinal parts of the thymus.3.CT densities of both cervical and mediastinal thymus were found to reduce with age, but the reduction was statistically significant only in the cervical thymus in this study. Conclusions CT densities of cervical and mediastinal components of the thymus may vary, with CT density of cervical thymus being lower. There is a positive correlation between CT densities of cervical and mediastinal parts of the thymus.CT density of cervical thymus reduces with age. Understanding these may help avoid confusion on CT and avoid the need for correlative USG, saving time and effort.